2011
DOI: 10.1186/1471-2148-11-372
|View full text |Cite
|
Sign up to set email alerts
|

The spatial scale of genetic subdivision in populations of Ifremeria nautilei, a hydrothermal-vent gastropod from the southwest Pacific

Abstract: BackgroundDeep-sea hydrothermal vents provide patchy, ephemeral habitats for specialized communities of animals that depend on chemoautotrophic primary production. Unlike eastern Pacific hydrothermal vents, where population structure has been studied at large (thousands of kilometres) and small (hundreds of meters) spatial scales, population structure of western Pacific vents has received limited attention. This study addresses the scale at which genetic differentiation occurs among populations of a western Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(82 citation statements)
references
References 66 publications
7
75
0
Order By: Relevance
“…For example, hidden genetic diversity and species crypticism was detected in gastropods of the genus Alviniconcha, where either two or three species were found to co-occur in NFB (A. kojimai, A. boucheti), MB (A. kojimai, A. boucheti) and LB (A. kojimai, A. boucheti, A. strummeri) . Populations of the snail Ifremeria nautilei were undifferentiated within and between NFB and LB, but genetically distinct from MB sites based on mitochondrial and microsatellite markers (Thaler et al 2011). As with our findings, the authors observed weak asymmetric movement from LB to NFB, in accordance with prevailing ocean currents.…”
Section: Discussionsupporting
confidence: 78%
“…For example, hidden genetic diversity and species crypticism was detected in gastropods of the genus Alviniconcha, where either two or three species were found to co-occur in NFB (A. kojimai, A. boucheti), MB (A. kojimai, A. boucheti) and LB (A. kojimai, A. boucheti, A. strummeri) . Populations of the snail Ifremeria nautilei were undifferentiated within and between NFB and LB, but genetically distinct from MB sites based on mitochondrial and microsatellite markers (Thaler et al 2011). As with our findings, the authors observed weak asymmetric movement from LB to NFB, in accordance with prevailing ocean currents.…”
Section: Discussionsupporting
confidence: 78%
“…Comparisons with Population Genetic Data. A recent population genetic study, using mitochondrial DNA and microsatellite markers, revealed that populations of the vent-restricted gastropod, Ifremeria nautilei, in the Manus Basin were genetically distinct from those of the North Fiji and Lau Basins (14). Estimates of gene flow also implied migration from the Lau to North Fiji Basin with a splitting time of tens of thousands of generations and genetic isolation between those two Basins and the Manus Basin for several hundred thousand generations.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic data imply that back-arc basin populations are well-mixed genetic pools (12,13). In contrast, vent populations in distant basins (∟3,000 km apart) are genetically distinct, suggesting that occasional migrations may have occurred over the course of several hundred thousand generations (14). There is one example of a widespread species (Bathymodiolus septemdierum complex) occurring in all western Pacific back-arc basins (15).…”
mentioning
confidence: 99%
“…This large-sized snail is one of the dominant gastropods of the hydrothermal vent fields of the south-west Pacific, and is becoming a model system of Abyssochrysoidea for population genetic and phylogeographic studies (Kojima et al, 2000;Suzuki et al, 2006;Thaler et al, 2011;Hidaka et al, 2012). The new mt genome sequence data of I. nautilei were combined with corresponding available data from other Caenogastropoda in order to elucidate its relative phylogenetic position.…”
Section: Snails Of the Superfamily Abyssochrysoidea (Gastropodamentioning
confidence: 99%